-8=-2(c+1)

Simple and best practice solution for -8=-2(c+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8=-2(c+1) equation:


Simplifying
-8 = -2(c + 1)

Reorder the terms:
-8 = -2(1 + c)
-8 = (1 * -2 + c * -2)
-8 = (-2 + -2c)

Solving
-8 = -2 + -2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2c' to each side of the equation.
-8 + 2c = -2 + -2c + 2c

Combine like terms: -2c + 2c = 0
-8 + 2c = -2 + 0
-8 + 2c = -2

Add '8' to each side of the equation.
-8 + 8 + 2c = -2 + 8

Combine like terms: -8 + 8 = 0
0 + 2c = -2 + 8
2c = -2 + 8

Combine like terms: -2 + 8 = 6
2c = 6

Divide each side by '2'.
c = 3

Simplifying
c = 3

See similar equations:

| 4r^2*4= | | 8x-5-3x=-15 | | 6x(2)-5x=2x | | X/7+4/7-x/5-3/5=4 | | 2x+1/2y=6 | | Y-160=-81/2(X-0) | | X+4/7-x-3/5=4 | | 1/6x=491/6 | | 30a=80+22a | | 4r^2*r= | | 6(x)=8x-3 | | 0=7/3x-7/2 | | 2/3(x)^2+7/3(x)=5 | | -16-10x=2(-7x+6) | | (x-7)*(x-6)= | | X-6=2x+12 | | 2/3x^2+7/3=5 | | d+c+(b-10)+(b+10)=360 | | (x-7)*(x+6)= | | 2a^2-a-12=2 | | 7m+15=9m-75 | | (4/8)(2/3)(1/5) | | X-6=2x-24 | | u(6u+5)=1 | | 6=-15x | | (3/5-3/10)*30 | | 76=-4m | | h=-16t^2+56t+40 | | x^3/2=14 | | 2(3.14)(12)= | | 0.125x=-3 | | b/2+5=-7 |

Equations solver categories